2003
DOI: 10.1182/blood-2002-03-0948
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in sickle cell disease: cardiac catheterization results and survival

Abstract: Few results on cardiac catheterization have been published for patients with sickle cell disease (SCD) with pulmonary hypertension (PHTN). Their survival once this complication develops is unknown. We analyzed hemodynamic data in 34 adult patients with SCD at right-sided cardiac catheterization and determined the relationship of PHTN to patient survival. In 20 patients with PHTN the average systolic, diastolic, and mean pulmonary artery pressures were 54.3, 25.2, and 36.0 mm Hg, respectively. For 14 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
273
2
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 307 publications
(299 citation statements)
references
References 24 publications
13
273
2
11
Order By: Relevance
“…It is associated with impaired exercise tolerance, progressive heart failure, and a high mortality [3,[11][12][13]. Therapies that are effective in primary pulmonary hypertension should be considered in symptomatic SCD patients with severe pulmonary hypertension [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with impaired exercise tolerance, progressive heart failure, and a high mortality [3,[11][12][13]. Therapies that are effective in primary pulmonary hypertension should be considered in symptomatic SCD patients with severe pulmonary hypertension [18].…”
Section: Discussionmentioning
confidence: 99%
“…Over a third of adults with SCD have elevated tricuspid jet velocity on Doppler echocardiography [85]. Individuals with SCD with elevated tricuspid regurgitant jet velocity (!3.0 cm/sec) have a 10-fold higher mortality rate than patients with SCD without elevated tricuspid regurgitant jet velocity [85,[88][89][90]. N-terminal probrain natriuretic peptide (NT-ProBNP) is also associated with catheterization detected pulmonary hypertension, and was identified as an independent predictor of death in the CSSCD and MSH cohorts [91,92].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…Pulmonary complications, acute chest syndrome (ACS) and PAH account for a large proportion of deaths in adults with SCD [3,4]. One retrospective study reported a median survival of 25.6 months for SCD patients with PAH confirmed by right heart catheterization [5]. Autopsy studies revealed that up to 75% of SCD patients have histological evidence of PAH [6].…”
Section: Introductionmentioning
confidence: 99%